Legalese and suits: uma proposta de glossário bilíngue de Colocações especializadas baseado em corpus - Vaz, Eurico Mayer (2025)
This research explores the extraction of specialized collocations and their syntactic- morphological and lexical-semantic analyses for the creation of a corpus-based bilingual glossary of specialized collocations in American English and Brazilian Portuguese. The ultimate goal of this research is to aid language users in navigating the specificities of legal terminology and to explore the lexicographic approach towards specialized language. The specialized collocations were extracted from a legal English corpus constituted of the subtitles from 134 episodes of the North-American TV Series “Suits”, named “Corpus Suits” (CS), which was submitted to analysis using the software Sketch Engine (Kilgariff et al, 2014). The comparable corpus English Web 2021 (enTenTen21), provided by the same software, was chosen in order to find evidence of usage and cooccurrence of the collocations beyond the scope of CS. The corpora were contrasted by usage of the Keywords tool from Sketch Engine in order to create a list of words that represent possible specific terminology, ordered by their keyness score. Fifteen nodes were elected from the Keywords to undergo further analysis with the Word Sketch tool searching for phraseological units that signal a high typicality score, indicating possibility of identifying as specialized collocations. Once the 42 candidates for specialized collocations were organized according to their frequency in the analyzed corpora, the tool Concordance was used to help understand the context they were used in the corpus. The context of usage guided a following classification of each of the nineteen selected collocations according to Hausmann's taxonomy (1985), feeding a table which compiles the collocation's frequency in each corpus, typicality score, syntactic-morphological formation and taxonomical classification. The table serves as input for the analysis of which classifications are predominant in this legal English extract, as well as for the construction of a bilingual glossary of specialized collocations, based on the methodological approach of Faulstich (2011) and analysis of a corpus of fifteen lexicographic products focused on legal terminology selected from the web. Furthermore, the corpus being constituted of a cultural product is an aspect which narrows the gap between academy and community, whom these results should serve in the first place. This research is anchored on the theoretical and methodological framework of corpus linguistics, lexicography and phraseology, especially regarding collocations and specialized collocations.